Investigating the effects of dhikr stimulation on auditory brainstem response : a case study of a healthy-normal hearing adult - Noor Alaudin Abdul Wahab,; Najihah Mohamad,; Muhammad Fida’Iy Nazi Nadin,; Nazrul Anuar Nayan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Dhikr has been studied to a limited extent in its impact on human auditory brainstem response. The article describes the processes involved in preparing Dhikr stimuli and analysing the auditory brainstem waves produced. A total of 18 words of ‘Allah’ recited by male and female Muslims were saved as 16 bit WAV files with sampling rates of 30,000 Hertz (Hz) and 1.09227 seconds (sec) with a sampling rate of 16 bits. Nevertheless, we calibrated and installed only six stimuli in Eclipse EP25 software. A healthy 23-year-old male underwent routine audiological examinations, including click ABR tests, for the purpose of ensuring normal hearing and brain stem function. To produce Dhikr-ABR waves, the subject listened to all six stimuli, initially presented at 100 dB peSPL to the left and right ear. Later, the tester reduced the intensity level and determined whether there were any significant peaks, namely DI, DIII, and DV, as well as IPLs and IALDs. There were robust waves associated with each stimulus. A few waves, however, displayed early peaks. Depending upon the presence or absence of peaks, the IPLs for DI-DIII, DIII-DV, and DI-DV would be about 2.0, 2.0, and 4.0 milliseconds, respectively. A reduction in intensity alters the amplitude and absolute latency of the waves.